Is the Public Aware of Water Quality Monitoring and Safety Notifications on Beaches? - Asli Aslan; Jeffery A. Jones; Dziyana Nazaruk; Sibel Zeki (Georgia Southern University, 2023)
Recreational water-related activities have important public health benefits, however, pollution at beaches may have serious health risks. Although there is a substantial amount of research and policies in place at federal and state levels, oftentimes these efforts may not be well translated to the public. This paper evaluates the effectiveness of routine water quality monitoring and warning systems in Georgia, USA. A survey was conducted among 238 beachgoers in Georgia, asking about awareness of water quality monitoring and warning signs for beach advisories. Surveys were collected directly at beaches as well as through an online questionnaire. Results show that more than a third of the respondents (36.1%) are unaware that Georgia beaches are monitored for water quality and public health with nearly two-thirds (64.7%) feeling current signage is inadequate. Most (89.9%) want signs to report the sources of pollution. Residents (compared to visitors), older, White, wealthier, and college-educated respondents are more likely to be aware of water monitoring. In terms of having ever read a water quality advisory, residents and older respondents are more likely to have read a warning. While most respondents have read such warning signs, a large percentage, 41.2%, have never read any beach advisory. Public health and environmental agencies must improve communications about polluted waters to the public using symbols and campaigns with a special emphasis on visitors and younger beachgoers.